FACTORS INFLUENCING CONSUMERS’ INTENTION TO USE ONLINE FOOD DELIVERY SERVICES AMONG WORKING ADULTS IN MALAYSIA - Lim Pei Chin; Chen Xiang; Alireza Mohammadi; He Sun (Journal of Islamic Management Studies, 2024)
The rising trend of online food delivery services (OFDS) is gaining popularity in Malaysia. This research aims to identify the factors that impact the intention of working adults in Malaysia to utilize OFDS. This study investigates the factors that influence consumers’ purchase intentions: convenience motivation, privacy and security, price savings, and perceived ease of use. This study adopts a quantitative research method, and 5-point Likert scale self-designed questionnaires will be distributed to 100 respondents. SPSS and Smart PLS are used to analyze the data. The findings show that convenience motivation, price saving, and perceived ease of use influence consumers’ intention to use OFDS significantly, while the factor of privacy and security is not significant. This research can inspire for OFDS providers to improve the features and functions of their products and services. It fills the gap that previous research has not focused on the specific factors, such as convenience motivation, privacy and security, price saving, and perceived ease of use that influence usage of online food delivery services (OFDS) among working adults in Malaysia. It can also help them consider price savings, which can attract new users to increase their OFDS application.